Analysis of Smoke Distribution in the Nusa Tenggara Islands Due to Forest and Land Fires - Simanjuntak, Ryan Juliston Pangihutan; Suarbawa, Komang Ngurah; Putra, I Ketut (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2022)
This study analyzes the distribution of smoke in the Nusa Tenggara Islands due to forest and land fires. This study uses secondary data in September 2020, such as satellite image data and meteorological condition data, because in 2020, the Nusa Tenggara Islands have the largest forest fires, NTT reaches 114,719.00 Ha, and NTB reaches 29,157.00 Ha. In this study, to detect smoke caused by forest and land fires, the Himawari-8 satellite and the Terra Aqua satellite will produce images to detect smoke. The image data will be processed using Satellite Animation and Interactive Diagnosis (SATAID) software for the Himawari-8 satellite and Hypersectral Data Viewer for Development of Research Applications (HYDRA) for the Terra Aqua satellite. The image results from the satellite will detect and show the distribution of smoke with the red, green, blue (RGB) technique, where the RGB technique will provide color contrast to the image object to be detected. Then the image results analyzed, and linked to the meteorological conditions that occurred during forest and land fires in the Nusa Tenggara Islands in September 2020 .